La innovación y la internacionalización del sector textil peruano: Un análisis a partir de microdatos. - Chang Rojas, Víctor (2024)
The Peruvian textile sector has been affected by international competition and the COVID-19 pandemic. Companies have streamlined their innovation processes to become more competitive internationally. The objective of the study is to identify the main innovation factors that influence the export of these companies in Peru. A Logit and Probit model was used for a sample of 327 textile companies from Peru in order to identify the impact of the main innovation factors on their export performance in 2018. The results show that innovation in internal Research and Development (R&D), innovation in Training for innovation activities, and innovation in Software and Database Development or acquisition, increase the probability of exporting. Furthermore, the results indicate that the probability of exporting is higher if companies have more years of business experience.